Factores claves de éxito en la implementación del lean manufacturing en organizaciones del sector de alimentos en Bogotá y sus alrededores (2022)
Lean manufacturing focuses on minimizing system waste through the rigorous use of resources to maximize activities that create value for the customer. The development of this research work is analyzed on the food sector due to the process of its production system, the perishability of the products and the way of generating added value in the different organizations through the lean methodology.